Effect of temperature on seed germination of queen palm Syagrus romanzoffiana (Cham.) glassman (Arecaceae) - Pivetta, KFL; de Paula, R. C.; Cintra, G. S.; Pedrinho, D. R.; Casali, L. P.; Pizetta, PUC; Pimenta, R. S. (International Society Horticultural Science, 2005)
The Syagrus romanzoffiana is a specie of the Arecaccae family, native of Brazil, frequently used in landscape architecture. Its propagation is by seeds, however, there is little information in the literature about seed germination of this ornamental palm. The objective of this work was to study the effects of temperatures on seed germination of Syagrus romanzoffliana. The experimental design used was entirely randomized, with six temperatures (20 degrees C, 25 degrees C, 30 degrees C and 35 degrees C, constant and 20-30 degrees C and 25-35 degrees C alternated), photoperiod of 12 hours, and five replications of 20 seeds each. The seeds were placed in plastic boxes with sand, counting daily germination until 43(th) day. The percentage of seed germination (43(th) day) and the speed germination index (SGI) were evaluated. The conclusion was that there was no germination at a constant temperature of 20 degrees C and in the alternated temperature of 20-30 degrees C; the higher germination percentages were verified in the constant temperatures of 30 degrees C and 35 degrees C that didn't differ statistically from the temperature of 25-35 degrees C. The germination was faster at a constant temperature of 30 degrees C.
Keywords: propagation; ornamental palm